Mempertimbangkan Hermeneutika sebagai Metode Tafsir Al-Qurâan - Maulana, Asep Shodiq (Jurnal Ilmu Dakwah, 2009)
Daâwah as process of actualizing Islamic message in theÂ  real life context in turn will weigh of grasp position to Al Quran text. Islamic massage is sent awayÂ  dialoguableÂ  with various socials environmental condition. In this condition it is needed one of relevant methodology in understanding Al-Qurâan.Â  The methodology is a method can catch meaning of text that cant only by rely grasp of language grammar corner only, but also socials context grasp of that text. That method is named hermeneutika.